Heat Stress Tolerance Gene FpHsp104 Affects Conidiation and Pathogenicity of Fusarium pseudograminearum - Xia, Huiqing; Chen, Linlin; Fan, Zhuo; Peng, Mengya; Zhao, Jingya; Chen, Wenbo; Li, Haiyang; Shi, Yan; Ding, Shengli; Li, Honglian (Frontiers in Microbiology, 2021)
Heat shock protein Hsp104, a homolog of the bacterial chaperone ClpB and plant Hsp100, plays an essential part in the response to heat and various chemical agents in Saccharomyces cerevisiae. However, their functions remain largely unknown in plant fungal pathogens. Here, we report the identification and functional characterization of a plausible ortholog of yeast Hsp104 in Fusarium pseudograminearum, which we termed FpHsp104. Deletion mutant of FpHsp104 displayed severe defects in the resisting of heat shock during F. pseudograminearum mycelia and conidia exposing to extreme heat. We also found that the protein showed dynamic localization to small particles under high temperature. However, no significant differences were detected in osmotic, oxidative, or cell wall stress responses between the wild-type and Δfphsp104 strains. Quantitative real-time PCR analysis showed that FpHsp104 was upregulated in the conidia, and disruption of the FpHsp104 gene resulted in defects in conidia production, morphology, and germination. The transcript levels of conidiation-related genes of FpFluG, FpVosA, FpWetA and FpAbaA were reduced in the Δfphsp104 mutant versus the wild-type strain, but heat-shocked mRNA splicing repair was not affected in Δfphsp104. Moreover, Δfphsp104 mutant also showed attenuated virulence, but its DON synthesis was normal. These data from the first study of Hsp104 in F. pseudograminearum strongly suggest that the FpHsp104 gene is an important element in the heat tolerance, development, and pathogenicity processes of F. pseudograminearum.